2018
DOI: 10.1002/ccd.27500
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy after coronary drug‐eluting stent implantation in China: A large single center study

Abstract: The 1-year DAPT after DES was applied to 97.3% of Chinese patients in the studied clinical center. However, the DAPT duration after 1 year was not adjusted according to the patients' bleeding situation and ischemic risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
1
1
Order By: Relevance
“…The biggest concern when considering prolongation of DAPT is the increased bleeding risk, especially in Chinese patients, who are considered to be at a relatively higher risk of bleeding. [19] In the present study, we found no significant difference in the risk of bleeding among the three DAPT groups. This result is in line with our previous finding that prolonging the duration of DAPT in patients undergoing PCI and patients with ACS did not significantly increase their risk of bleeding, including all bleeding events and major bleeding events, [7,20] and confirms the safety of prolonging DAPT.…”
Section: Prolonging Dapt Does Not Increase the Bleeding Riskcontrasting
confidence: 52%
“…The biggest concern when considering prolongation of DAPT is the increased bleeding risk, especially in Chinese patients, who are considered to be at a relatively higher risk of bleeding. [19] In the present study, we found no significant difference in the risk of bleeding among the three DAPT groups. This result is in line with our previous finding that prolonging the duration of DAPT in patients undergoing PCI and patients with ACS did not significantly increase their risk of bleeding, including all bleeding events and major bleeding events, [7,20] and confirms the safety of prolonging DAPT.…”
Section: Prolonging Dapt Does Not Increase the Bleeding Riskcontrasting
confidence: 52%
“…BARC 2 bleeding or greater was independently associated with shortening DAPT duration. 32 BARC 2 bleeding events might not be life threatening but could lead to discontinuation or noncompliance of antiplatelet therapy, which was associated with a substantially increased risk of major adverse cardiovascular events. 33 An increased mortality associated with BARC 2 bleeding was reported in the TRACER (Thrombin Receptor Antagonist for Clinical Event Reduction in Acute Coronary Syndrome) study.…”
Section: Discussionmentioning
confidence: 99%